PENGARUH KOMPENSASI, DISIPLIN, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT SEMANGAT SEJAHTERA BERSAMA JAYAKARTA - Peri; Meslo Perdede; Heles Eriyanto; Alfreid Lazuardi (Sekolah Tinggi Ilmu Ekonomi Bisnis Indonesia, 2023)
The purpose of this study was to determine the effect of variable compensation, discipline, and job motivation toward employees performance. The research method uses associative. Based on the results of the discussion the following conclusions are obtained: Test results partially for compensation variable with statistic values tcount< ttable (0.574 < 1.985) and probability values of 0.567 > 0.05, then Ho is accepted means there is influence significant from the compensation variable toward employees performance. Partial test results for discipline variables with statistic values tcount> ttable (2.962 > 1.985) and probability values of 0.004 < 0.05, then Ho is rejected means there is influence significant from the discipline variable toward employees performance. Partial test results for motivation job variables with statistic values tcount> ttable (2.017 > 1.985) and probability values of 0.046 < 0.05, then Ho is rejected means there is influence significant from the job motivation variable toward employees performance. Simultaneous test results with a value of Fcount> Ftable (31.918 > 2.700) and probability values of 0.000 < 0.05, then Ho is rejected or Ha is accepted which means that there is a significant simultaneous influence (together) of the variable compensation, discipline, and job motivation toward employees performance. The magnitude of the correlation coefficient (R) is 0.707 which means that there is a moderate correlation between compensation, discipline, and job motivation toward employees performance. The amount of the adjusted coefficient of determination (adjusted R2) is 0.484 or 48.4%, which means that the independent variables can explain the changes in the variable employees performance by 48.4% while the remaining 51.6% is explained by other factors outside the research this.